Effect of directed training on reader performance for CT colonography: multicenter study. - European Society of Gastrointestinal and Abdominal Radiology CT Colonography Group Investigators (2007)
PURPOSE: To define the interpretative performance of radiologists experienced in computed tomographic (CT) colonography and to compare it with that of novice observers who had undergone directed training, with colonoscopy as the reference standard. MATERIALS AND METHODS: Physicians at each participating center received ethical committee approval and followed the committees' requests regarding informed consent. Nine experienced radiologists, nine trained radiologists, and 10 trained technologists from nine centers read 40 CT colonographic studies selected from a data set of 51 studies and modeled to simulate a population with positive fecal occult blood test results: Studies were obtained in eight patients with cancer, 12 patients with large polyp, four patients with medium polyp, and 27 patients without colonic lesions. Findings were verified with colonoscopy. An experienced radiologist used 50 endoscopically validated studies to train novice observers before they were allowed to participate. Observers used one software platform to read studies over 2 days. Responses were collated and compared with the known diagnostic category for each subject. The number of correctly classified subjects was determined for each observer, and differences between groups were examined with bootstrap analysis. RESULTS: Overall, 28 observers read 1084 studies and detected 121 cancers, 134 large polyps, and 33 medium polyps; 448 healthy subjects were categorized correctly. Experienced radiologists detected 116 lesions; trained radiologists and technologists detected 85 and 87 lesions, respectively. Overall accuracy of experienced observers (74.2%) was significantly better than that of trained radiologists (66.6%) and technologists (63.2%). There was no significant difference (P=.33) between overall accuracy of trained radiologists and that of technologists; however, some trainees reached the mean performance achieved by experienced observers. CONCLUSION: Experienced observers interpreted CT colonographic images significantly better than did novices trained with 50 studies. On average, no difference between trained radiologists and trained technologists was found; however, individual performance was variable and some trainees outperformed some experienced observers.